2010
DOI: 10.1007/s12311-010-0232-3
|View full text |Cite
|
Sign up to set email alerts
|

Superior Cerebellar Peduncle Atrophy in Friedreich’s Ataxia Correlates with Disease Symptoms

Abstract: Friedreich's ataxia (FRDA) is the most common early onset inherited ataxia with clinical manifestations, including gradual progression of unremitting cerebellar-sensory ataxia, peripheral sensory loss, loss of lower limb tendon reflexes and hypertrophic cardiomyopathy. Although atrophy of the superior cerebellar peduncle (SCP) has been reported in several magnetic resonance imaging (MRI) studies of FRDA, the relationship of SCP changes to genetic and clinical features of FRDA has not been investigated. We acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 42 publications
(54 reference statements)
7
48
1
Order By: Relevance
“…However, other studies also failed to find significant correlations with cerebellar GM volume (Prakash et al, 2009;Akhlaghi et al, 2011) and found the ataxia score to be correlated with other metrics related to the cerebellar peduncles -dMRI metrics (Prakash et al, 2009) and volume metrics (Akhlaghi et al, 2011). This suggests that total cerebellar GM volume may not be the most sensitive marker of general ataxia score and a measure of the integrity of the cerebellar peduncles may be preferable, but only a very few studies have investigated correlation between ataxia score and dMRI metrics in cerebellar peduncles.…”
Section: White Matter Damage and Clinical Scorementioning
confidence: 99%
“…However, other studies also failed to find significant correlations with cerebellar GM volume (Prakash et al, 2009;Akhlaghi et al, 2011) and found the ataxia score to be correlated with other metrics related to the cerebellar peduncles -dMRI metrics (Prakash et al, 2009) and volume metrics (Akhlaghi et al, 2011). This suggests that total cerebellar GM volume may not be the most sensitive marker of general ataxia score and a measure of the integrity of the cerebellar peduncles may be preferable, but only a very few studies have investigated correlation between ataxia score and dMRI metrics in cerebellar peduncles.…”
Section: White Matter Damage and Clinical Scorementioning
confidence: 99%
“…1 However, the few reports mentioning cerebellar atrophy in FRDA were invariably based on subjective visual assessment of the cerebellar size or were focused on patients with late-onset FRDA, while morphometric assessment failed to show decreased cerebellar volume in patients with FRDA with typical disease onset before 25 years of age compared with agematched controls. 2 Lack of cortical cerebellar atrophy in FRDA was confirmed in a voxel-based morphometry study that, however, demonstrated volume loss of the deep peridentate WM. 3 Preservation of the cortex is in line with the pathologic descriptions of FRDA emphasizing that cerebellar damage involves the dentate nuclei and deep cerebellar WM.…”
mentioning
confidence: 92%
“…4 A nonspecific finding emerging in FRDA is atrophy and microstrutural damage of the superior cerebellar peduncles that are correlated with disease duration and severity of the neurologic deficit. 2,3 Because the superior cerebellar peduncle contains most of the efferent fibers of the dentate nucleus, which is a site of primary neurodegeneration in FRDA, 4 the superior cerebellar peduncle alteration appears a promising biomarker for this disease but is not visually apparent and requires morphometry or computation of DTI measurements to be detected. Also, the increased magnetic susceptibility effects due to iron deposition observed in the cerebellar dentate nuclei of patients with FRDA require specific T2*acquisitions and postprocessing.…”
mentioning
confidence: 99%
“…In addition, Akhlaghi et al (37) have demonstrated that superior cerebellar peduncle atrophy is correlated to onset age, disease duration, and weight of clinical findings. From neuroimaging, cerebellar atrophy and spinal atrophy were determined in 33.8% and 11.7% of our FA cases, respectively, while cerebellar atrophy was diagnosed in the two SCA6 cases but spinal atrophy was not observed.…”
Section: Discussionmentioning
confidence: 99%